Nose to brain delivery of antiretroviral drugs in the treatment of neuroAIDS - Anupam Sarma (Molecular Biomedicine, 2020)
Abstract NeuroAIDS (Neuro Acquired Immunodeficiency Syndrome) or HIV (Human Immunodeficiency Virus) associated neuronal abnormality is continuing to be a significant health issue among AIDS patients even under the treatment of combined antiretroviral therapy (cART). Injury and damage to neurons of the brain are the prime causes of neuroAIDS, which happens due to the ingress of HIV by direct permeation across the blood-brain barrier (BBB) or else via peripherally infected macrophage into the central nervous system (CNS). The BBB performs as a stringent barricade for the delivery of therapeutics drugs. The intranasal route of drug administration exhibits as a non-invasive technique to bypass the BBB for the delivery of antiretroviral drugs and other active pharmaceutical ingredients inside the brain and CNS. This method is fruitful for the drugs that are unable to invade the BBB to show its action in the CNS and thus erase the demand of systemic delivery and thereby shrink systemic side effects. Drug delivery from the nose to the brain/CNS takes very less time through both olfactory and trigeminal nerves. Intranasal delivery does not require the involvement of any receptor as it occurs by an extracellular route. Nose to brain delivery also involves nasal associated lymphatic tissues (NALT) and deep cervical lymph nodes. However, very little research has been done to explore the utility of nose to brain delivery of antiretroviral drugs in the treatment of neuroAIDS. This review focuses on the potential of nasal route for the effective delivery of antiretroviral nanoformulations directly from nose to the brain.